If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5n(n + 6) = -5 Reorder the terms: 5n(6 + n) = -5 (6 * 5n + n * 5n) = -5 (30n + 5n2) = -5 Solving 30n + 5n2 = -5 Solving for variable 'n'. Reorder the terms: 5 + 30n + 5n2 = -5 + 5 Combine like terms: -5 + 5 = 0 5 + 30n + 5n2 = 0 Factor out the Greatest Common Factor (GCF), '5'. 5(1 + 6n + n2) = 0 Ignore the factor 5.Subproblem 1
Set the factor '(1 + 6n + n2)' equal to zero and attempt to solve: Simplifying 1 + 6n + n2 = 0 Solving 1 + 6n + n2 = 0 Begin completing the square. Move the constant term to the right: Add '-1' to each side of the equation. 1 + 6n + -1 + n2 = 0 + -1 Reorder the terms: 1 + -1 + 6n + n2 = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 6n + n2 = 0 + -1 6n + n2 = 0 + -1 Combine like terms: 0 + -1 = -1 6n + n2 = -1 The n term is 6n. Take half its coefficient (3). Square it (9) and add it to both sides. Add '9' to each side of the equation. 6n + 9 + n2 = -1 + 9 Reorder the terms: 9 + 6n + n2 = -1 + 9 Combine like terms: -1 + 9 = 8 9 + 6n + n2 = 8 Factor a perfect square on the left side: (n + 3)(n + 3) = 8 Calculate the square root of the right side: 2.828427125 Break this problem into two subproblems by setting (n + 3) equal to 2.828427125 and -2.828427125.Subproblem 1
n + 3 = 2.828427125 Simplifying n + 3 = 2.828427125 Reorder the terms: 3 + n = 2.828427125 Solving 3 + n = 2.828427125 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + n = 2.828427125 + -3 Combine like terms: 3 + -3 = 0 0 + n = 2.828427125 + -3 n = 2.828427125 + -3 Combine like terms: 2.828427125 + -3 = -0.171572875 n = -0.171572875 Simplifying n = -0.171572875Subproblem 2
n + 3 = -2.828427125 Simplifying n + 3 = -2.828427125 Reorder the terms: 3 + n = -2.828427125 Solving 3 + n = -2.828427125 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + n = -2.828427125 + -3 Combine like terms: 3 + -3 = 0 0 + n = -2.828427125 + -3 n = -2.828427125 + -3 Combine like terms: -2.828427125 + -3 = -5.828427125 n = -5.828427125 Simplifying n = -5.828427125Solution
The solution to the problem is based on the solutions from the subproblems. n = {-0.171572875, -5.828427125}Solution
n = {-0.171572875, -5.828427125}
| 16y-4y=-40 | | 10(x+2)+8x=8x+30 | | -2x-x=15 | | 120x+60=30x+90 | | 3=10y-1/2(6y-2) | | 0=2m+6m | | -11=4x-1-2 | | -3.9+6.1=4x-2.6-3x | | 2(5x+4)=7x+12 | | 1+5a+6a=12 | | 9.9-47.8z=-2.8z-3(9z-0.3) | | 4h+14-2h=9-(2-3h) | | x^2+11x-350=0 | | 15-(2)*d=3 | | 5n(n+6)=-5n | | 45-x+36=125 | | -16=2n-6n | | 2=6r-4r | | 1+5n+3n=17 | | 3x+5/2=5/3 | | -8=4n+2-2n | | 35+23+3x=52+45 | | -4x-5x=-9 | | -6x+3x=-18 | | 16-3x+4x=27 | | -1.1-17.6k=-7.6k+3(-3-1.7) | | -6b-1+b=-6 | | 2x+35=52 | | 1-3x=-14+2x | | 1+5x-6=-15 | | 5y+2+2y=23 | | I=60000*13.5*21 |